Kindergarten Teachers' Professional Commitment to Baptist Charity Nursery School - Tamara Takács (Educaţia 21)
Today, social inclusion and exclusion are becoming increasingly important issues in society. The concept of social exclusion focuses on the process whereby certain disadvantages and risk factors prevent individuals from successfully integrating. The risk of social exclusion in Ibrány, the location of the research, is significant. Education especially early education is very important in catching up. So, kindergartens in disadvantaged areas play a key role in inclusion. An important question is what motivates teachers and childcare professionals in these areas? What keeps them in the field and how can they motivate children? And what problems they face every day and how they solve them? During the research, interviews were conducted with nine staff members at the Baptist Charity Nursery School, including the head of the nursery, five nursery teachers and three nursery nannies. Most of the children in this nursery are from a multiply disadvantaged background and most of them are also Roma. The kindergarten has a total of 64 children in three groups: small, medium and large. The data was collected in March 2024. The interview texts were analyzed using the content analysis method. The survey provides feedback on how teachers feel about a kindergarten where children from a disadvantaged background are most likely to attend, and the role of pre-school education in overcoming disadvantage which can serve as a lesson for the training of future pre-school teachers.